Determinants of Murabahah Margin Income: A Study on Sharia Commercial Banks in Indonesia - Ade Ananto Terminanto; Taufiq Ramadhan (Universitas Darunnajah, 2025)
The aim of this research is whether the overhead cost, risk cost and wadiah savings variables have a partial and simultaneous effect on murabahah margin income at Islamic commercial banks. This research method uses a quantitative approach, This research method uses a quantitative approach, the data used is secondary data. The sampling technique in this research used saturated samples to obtain a sample of 32. The data collection technique in this research used documentation and literature study. This research uses multiple linear regression analysis. The results of this research show that partially the overhead cost variable has an effect on murabahah margin income, risk costs do not have a significant effect on murabahah margin income while wadiah savings have a significant effect on murabahah margin income. The conclusion of this research is that the overhead cost variable has an effect because the margin expected by the bank is influenced by the size of the overhead costs borne by the bank, risk costs have no effect because the majority of murabahah financing is channeled to finance consumption which is classified as minimal risk, while wadiah savings have an effect, indicating that there is a lot of interest. people to save their funds in sharia commercial banks, especially wadiah deposits.